2023
DOI: 10.1007/s00221-023-06619-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vestibulo-ocular reflex and its adaptation during stop-and-go car rides in motion sickness susceptible passengers

Abstract: Motion sickness is a physiological condition that negatively impacts a person's comfort and will be an emerging condition in autonomous vehicles without proper countermeasures. The vestibular system plays a key role in the origin of motion sickness. Understanding the susceptibility and (mal) adaptive mechanisms of the highly integrated vestibular system is a prerequisite for the development of countermeasures. We hypothesize a differential association between motion sickness and vestibular function in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…The findings demonstrated that suppressing predisposing factors that are thought to induce ride discomfort will support passengers in feeling comfortable while travelling by minibuses. These findings are consistent with those of prior studies conducted by scholars in various locations and at various times [ 20 , 26 , 27 ]. All of the research described above advised countermeasures that could be viewed as model-based motion control systems for transportation authorities, but they did not focus on what and how suppression actions were performed by placing them in the social context.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The findings demonstrated that suppressing predisposing factors that are thought to induce ride discomfort will support passengers in feeling comfortable while travelling by minibuses. These findings are consistent with those of prior studies conducted by scholars in various locations and at various times [ 20 , 26 , 27 ]. All of the research described above advised countermeasures that could be viewed as model-based motion control systems for transportation authorities, but they did not focus on what and how suppression actions were performed by placing them in the social context.…”
Section: Resultssupporting
confidence: 93%
“…Travel discomfort suppression methods are steps that can be taken to lessen or prevent people from feeling ill because of exposure while traveling in vehicles [ 25 , 26 ]. The findings demonstrated that suppressing predisposing factors that are thought to induce ride discomfort will support passengers in feeling comfortable while travelling by minibuses.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional sine harmonic acceleration (SHA) around the vertical axis is limited to detecting the aVOR function in the low-frequency region of the lateral semicircular canal. Although vHIT can detect all six semicircular canals, it only detects the aVOR function in the high-frequency region of each semicircular canal ( Liu et al, 2023 ; Ramaioli et al, 2023 ). Despite many studies ( Baloh et al, 1986 ; Iida et al, 2001 ; Young et al, 2001 ) have explored methods to detect the low-frequency region of the vertical semicircular canal, their clinical applicability remains limited due to the high cost, invasiveness, age restrictions, and difficulties of head position control.…”
Section: Discussionmentioning
confidence: 99%